2022
DOI: 10.21203/rs.3.rs-1965780/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of core stability and feedback music on upper body mediolateral movements during cycling

Abstract: Asymmetry in involuntary trunk motion may be related to core stability. If core stability properly controls postural stability during distal segment movements, trunk motion should be symmetric. Based on the assumption that head motion partially represents trunk motion, we developed a system that measures head angle and provides feedback music on head motion. If the head angle exceeds a predefined threshold, the music is muted in the earbud on the side of the head tilt. To investigate the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recently, our group demonstrated that mediolateral head motion during cycling can be used to estimate core stability status, as determined by the SCST. 13 The poor core stability group, as defined by the SCST, exhibited greater laterally asymmetrical head motion than the good core stability group during cycling. The reaction force generated by pedaling causes lateral movement of the trunk.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, our group demonstrated that mediolateral head motion during cycling can be used to estimate core stability status, as determined by the SCST. 13 The poor core stability group, as defined by the SCST, exhibited greater laterally asymmetrical head motion than the good core stability group during cycling. The reaction force generated by pedaling causes lateral movement of the trunk.…”
Section: Introductionmentioning
confidence: 87%